Living Conditions and sociocultural factors behind hydrocarbon and heavy metal exposure in amazon indigenous people - Portocarrero, Julio (2018)
The present descriptive review seeks to identify the living conditions and the sociocultural factors behind the risks of exposure to heavy metals and metalloids in the indigenous Amazonian context, principally in Peru and Ecuador. The results suggest that the exhibition to heavy metals and metalloids in indigenous population is multifactorial, combining aspects like: the presence of extractive activity, fishing and hunt patterns, historical precedents of anthropogenic and natural sources; patterns of food preparation, storage and consumption; water sources and processing; work division and industrial material reutilization.